A Landscape of Travel The Work of Tourism in Rural Ethnic China - Chio, Jenny T. (Studies on Ethnic Groups in China, 2014)
Open-access edition: DOI 10.6069/9780295805061 While the number of domestic leisure travelers has increased dramatically in reform-era China, the persistent gap between urban and rural living standards attests to ongoing social, economic, and political inequalities. The state has widely touted tourism for its potential to bring wealth and modernity to rural ethnic minority communities, but the policies underlying the development of tourism obscure some complicated realities. In tourism, after all, one person's leisure is another person's labor. A Landscape of Travel investigates the contested meanings and unintended consequences of tourism for those people whose lives and livelihoods are most at stake in China's rural ethnic tourism industry: the residents of village destinations. Drawing on ethnographic research conducted in Ping'an (a Zhuang village in Guangxi) and Upper Jidao (a Miao village in Guizhou), Jenny Chio analyzes the myriad challenges and possibilities confronted by villagers who are called upon to do the work of tourism. She addresses the shifting significance of migration and rural mobility, the visual politics of tourist photography, and the effects of touristic desires for "exotic difference" on village social relations. In this way, Chio illuminates the contemporary regimes of labor and leisure and the changing imagination of what it means to be rural, ethnic, and modern in China today. More about the author: http://www.jennychio.com/